The U.S. Army and the new national security strategy - Davis, Lynn E. (Lynn Etheridge), 1943-; Shapiro, Jeremy; Arroyo Center; Rand Corporation (Santa Monica, CA : RAND, 2003)
How is the U.S. Army changing to fulfill its role in light of the new national security strategy? How must it change further to better accomplish its manifold and varied missions? How did the attacks of September 11, 2001, alter or accelerate the need for change? Is the Army's far-reaching program for change known as the Army Transformation on the right track? Fourteen RAND analysts with broad experience in strategic and Army planning have undertaken to answer these questions. In this book, the authors use nine chapters to examine the Army's role in the offensive war on terrorism; the Army's homeland security needs; the implications for the Army of the increase in emphasis on the Asia-Pacific region; the Army's role in coalition operations; the unfinished business of jointness-the lessons to be learned from recent Army operations and how the Army can better prepare for the future; the Army's deployability, logistical, and personnel challenges; and whether the Army can afford the Transformation as currently envisaged. These chapters are bracketed by a concise introduction, a description of the new national security strategy and the Army's place in it, and a succinct summary of the authors' conclusions. This book is nothing less than a call for the Army to change and a prescription for what needs to be done.
ch. 1. Introduction / Lynn E. Davis, Jeremy Shapiro -- ch. 2. New national security strategy / Jeremy Shapiro, Lynn E. Davis -- ch. 3. U.S. Army and the offensive war on terrorism / Bruce R. Nardulli -- ch. 4. Defining the Army's homeland security needs / Lynn E. Davis -- ch. 5. Shift to Asia, implications for U.S. land power / Roger Cliff, Jeremy Shapiro -- ch. 6. Preparing for coalition operations / Nora Bensahel -- ch. 7. Transformation and the unfinished business of jointness, lessons for the Army from the Persian Gulf, Kosovo, and Afghanistan / Bernard Rostker -- ch. 8. Preparing the Army for joint operations / Bruce Pirnie -- ch. 9. Moving rapidly to the fight / John Gordon, David Orletsky -- ch. 10. Taking care of people, the future of Army personnel / Susan Hosek -- ch. 11. Making the power projection Army a reality / Eric Peltz, John Halliday -- ch. 12. Resourcing the twenty-first century Army / David Kassing -- ch. 13. Refining Army transformation / Thomas L. McNaugher.
"MR-1657-A"--Page 4 of cover
"Prepared for the United States Army."
Includes bibliographical references.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
Keywords: United States. -- Army; États-Unis. -- Army; United States. -- Army; National security -- United States; World politics -- 21st century; United States -- Military policy; Politique mondiale -- 21e siècle.; HISTORY -- Military; POLITICAL SCIENCE -- Security (National & International); Military policy; National security; World politics; United States; National security -- United States; World politics -- 21st century; 2000-2099